Integrated Pest Management (IPM) of the Tawny Crazy Ant, Nylanderia fulva (Mayr) - Faith Oi; Dawn Calibeo; John Page; Michael Bentley (EDIS, 2016)
The tawny crazy ant infests buildings and greenhouses, attacks crops, domestic animals, and honeybee hives, displaces native ant species, and disrupts electrical equipment. This 8-page fact sheet is a major revision that describes how to identify the ant and monitor for infestations. It explains how to eliminate food sources and harborages and presents an integrated pest management plan and specific approaches to control this pest ant. (Note: the tawny crazy ant is a serious pest that multiplies quickly and can easily become an overwhelming problem. If you suspect you have tawny crazy ants, the best approach is to call a licensed pest-control professional for help). Written by Faith Oi, Dawn Calibeo, John Paige III, and Michael Bentley, and published by the UF Department of Entomology and Nematology, September 2016.